Morphometric study of southern velvet shrimp (Metapenaeopsis palmensis) captured during the night in the waters of Samboja, Kutai Kartanegara Regency - Anggi Dhafana Putri; Abdunnur Abdunnur; Muhammad Syahrir Ramang (Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
Southern valvet shrimp (M. palmensis) is one of the shrimps with the Penaidae family, morphometric measurements are carried out in order to see the things that affect the shape of the species. This study aimed to provide information about the morphometric study of South valvet shrimp (M. palmensis) caught in the waters of Samboja, Kutai Kartanegara. This research was conducted in Samboja Waters, Kutai Kartanegara, in November-Desember 2022. The sample used was 250 Southern valvet shrimp (M. palmensis). Morphometric studies on Southern valvet shrimp (M. palmensis) used analysis with the analysis of covariant (ANCOVA) test to see the 18 morphometric covariates that affect the total length (PTO). Based on the results of the analysis of the ANOVA univariate test, it was found that 18 morphometrics had a significant value < 0.05 which means H1 was accepted, that all morphometrics affect PTO. Furthermore, the ANCOVA analysis was carried out, the results were 9 morphometrics which had sig <0.05, namely, head length (PK), length of the fourth internode (PRE), length of the sixth internode (PRN), headless length (PTK), length of the third lower segment (PTB), length of the fourth lower segment (PEB), length of the fifth lower segment (PLB), length of the sixth lower segment (PNB) and length of the tail (PE). Based on the results of the ANCOVA test. the most significant morphometric that influenced PTO was the 9 morphometry.